Juridical Review of Human Trafficking as a Transnational Crime - Simangunsong , Rini T; Situmeang, Dina M (Yayasan Kawanad, 2025)
Human trafficking across national borders represents a critical challenge to Indonesia's national security and human rights protection. This study aims to evaluate the effectiveness of international cooperation mechanisms in counter-trafficking efforts and analyze the strategic approaches implemented by Lemhannas RI (Indonesia's National Resilience Institute) and BNPP (National Border Management Agency) in combating transnational crime at Indonesia's borders. This research employs a descriptive-qualitative methodology through document analysis, policy review, and examination of legal frameworks, including the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW, ratified through Law No. 7/1984), Law No. 21/2007 on Human Trafficking Eradication, and the Palermo Protocol standards. The results reveal that while Indonesia has established a progressive legal framework, implementation faces challenges due to economic disparities, demographic pressures, and patriarchal norms. International cooperation mechanisms show limited effectiveness due to jurisdictional complexities and weak cross-border coordination. The strategic approaches by Lemhannas RI and BNPP require strengthened inter-agency collaboration and enhanced border control mechanisms, particularly in vulnerable maritime regions. The study concludes that effective human trafficking eradication demands an integrated approach combining robust law enforcement, enhanced international cooperation, and targeted socio-economic interventions. Recommendations include strengthening maritime border surveillance, developing comprehensive victim protection programs, and establishing more effective international cooperation mechanisms.